1999
DOI: 10.1063/1.125516
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite CoPt:C films for extremely high-density recording

Abstract: Nanocomposite CoPt:C films were investigated as potential media for extremely high-density recording. An annealing temperature of over 600 °C is necessary to form nanocomposite CoPt:C films consisting of C matrix and fct CoPt nanocrystallites with grain sizes of 8–20 nm and coercivities of 3–12 kOe. Coercivity and grain size increase with increasing annealing temperature and decreasing C concentration and they are insensitive to film thickness. The average activation volumes are about 0.9×10−18 cm3. The proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
1
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 162 publications
(72 citation statements)
references
References 14 publications
1
66
1
4
Order By: Relevance
“…6͑a͔͒; ͑ii͒ the sample was exposed to a field gradient of low intensity ͑0.4 kOe͒, where the angle between the magnetic field and the sample changed from 45°to 135°; ͑iii͒ spectrum recorded on sample exposed to a field of 0. 4 kOe applied perpendicular to the ␥ beam ͓Fig. 6͑b͔͒; and ͑iv͒ zero field spectrum recorded after removing the field ͓Fig.…”
Section: B Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…6͑a͔͒; ͑ii͒ the sample was exposed to a field gradient of low intensity ͑0.4 kOe͒, where the angle between the magnetic field and the sample changed from 45°to 135°; ͑iii͒ spectrum recorded on sample exposed to a field of 0. 4 kOe applied perpendicular to the ␥ beam ͓Fig. 6͑b͔͒; and ͑iv͒ zero field spectrum recorded after removing the field ͓Fig.…”
Section: B Magnetic Propertiesmentioning
confidence: 99%
“…Examples of current interest include magnetically hard and soft metallic alloys, 1 core-surface nanoparticles, 2 and nanocomposite films. 3,4 Recently, a new magnetic behavior has been observed at low temperature ͑5 K͒ in insulating composites based on crystalline ␥-Fe 2 O 3 ͑maghemite͒ nanoparticles dispersed in a solid polymer matrix, 5 prepared by freezing a methanol based ferrofluid of the composite: magnetic particles have been observed rotating freely in response to an applied static magnetic field ͑i.e., ''free rotor behavior''͒ after conditioning the material in a cycling magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…One way to solve this problem is to use nanocomposite films, in which the grain growth can be suppressed by nonmagnetic matrix. 6,7 For example, the studies of CoPt:C, 8,9 FePt:B 2 O 3 , 10,11 and CoPt:B 2 O 3 12 films have been reported. In this study, rapid thermal annealing processing conditions and the nanostructural and magnetic properties of FePt:Ag films are presented.…”
Section: Introductionmentioning
confidence: 99%
“…By controlling the thickness, composition, and annealing conditions, and/or depositing a proper underlayer, nearly perfect ͑001͒-oriented CoPt and FePt films can be obtained. Recently, L1 0 structured CoPt and FePt films, [1][2][3][4] CoPt and FePt based nanocomposite films 5,6 and FePt selfassembled nanoparticles 7 have attracted much attention. These high anisotropy materials show great potential for high-density magnetic recording because of their ability to achieve extremely small grain sizes.…”
mentioning
confidence: 99%